Molecular genetics and patient management of multiple endocrine neoplasia type I - Thakker, R (2001)
Multiple endocrine neoplasia type 1 (MEN-1) is an autosomal dominant disorder characterized by the combined occurrence of tumours of the parathyroids, pancreatic islet cells and anterior pituitary. Other MEN-1-associated tumours include angiofibromas, collagenomas, lipomas, carcinoids and adrenocortical tumours. The MEN-1 gene, which represents a putative tumour suppressor gene, was identified in 1997, and over 340 mutations have been reported in MEN-1 families, patients with non-familial MEN-1, families with isolated primary hyperparathyroidism and those with sporadic non-MEN-1 endocrine tumours. The mutations are scattered throughout the nine exons that encode a 610 amino acid nuclear protein (MENIN), which interacts with the transcriptional factor JunD. These recent developments have made it possible to consider genetic screening for this inherited disorder.